Treatment of Class II right subdivision maloclussions without extractions. Case report - Borja-Sihuinta, Fadiath (2018)
Class II subdivision treatments require tooth symmetry as well as the midline. Most of these cases are of dentoalveolar origin, but there are certain cases in which it is a combination of skeletal origin as dentoalveolar. This article reports the orthodontic treatment of a Class II division II malocclusion right subdivision without extraction of a patient with brachyfacial, asymmetric biotype, straight total profile, labial retrusion, skeletal Class II, deviation of the upper and lower middle line, moderate crowding and retruded incisors. The treatment of extractions should be as an alternative treatment of the initial clinical characteristics of the patient.